Euro area inflation differentials: The role of fiscal policies revisited - Cristina Checherita-Westphal; Nadine Leiner-Killinger; Teresa Schildmann (European Central Bank (ECB), 2023)
This paper provides a comprehensive empirical analysis of the role of discretionary fiscal policy for inflation differentials across the 19 euro area countries over the period 1999-2019. The results confirm existing (older) literature that it is difficult to find robust evidence of the fiscal policy stance or impulse impacting directly on inflation differentials. We do find, however, support for an indirect effect of discretionary fiscal policy on inflation differentials working through the output gap channel. There is also some evidence that fiscal policy may be especially potent in influencing inflation differentials - with fiscal tightening cooling (and fiscal expansion increasing) inflation pressures - when the economy is above its potential. Finally, going from the overall fiscal stance or impulse to individual fiscal instruments, we find that value added tax (VAT) rate changes and public wage growth are statistically significant determinants of inflation differentials in our sample.
Keywords: E31; E62; E63; F45; 330; Fiscal policy; inflation differentials; tax policy; public wages